In vitro effect of the protein extract of Sarcocystis aucheniae macrocysts on the viability and degranulation of rabbit (Oryctologus cuniculus) leukocytes - Inga, María del Carmen (2016)
The aim of this study was to determine the in vitro toxic effect of the protein extract of macrocysts of Sarcocystis aucheniae on circulating rabbit leukocytes (cytotoxicity). Five concentrations of the protein extract (0.5, 1, 50, 500, 1000 ng/100 μl) were exposed to a population of 500 000 leukocystes/ml for 1 and 12 h in a culture medium at 37 °C. The cell viability was evaluated by trypan blue exclusion and the enzyme degranulation of leukocytes (myeloperoxidase and glucosaminidase ) by polyacrylamide gel electrophoresis and transfered to nitrocellulose membranes (Western blotting). The cell count at 1 h of incubation showed high mortality (57.7 to 58.1%), whereas at 12 h varied from 65.2 to 99.4%, and without statistical differences between the mean of leukocytes that survive in each treatment. Mortality in the control group (saline) was 5 and 57% at 1 and 12 h of incubation respectively. On leukocyte degranulation the inoculated groups secreted different proteins than the control group inoculated with saline as evidenced by staining bands in controlling protein transfer membranes. It was concluded that the protein extract of S. aucheniae macrocysts is highly cytotoxic to rabbit leukocytes and protein secretion is observed.